Revitalisasi Perkebunan Karet Rakyat Melalui Pendekatan Kawasan Industri Masyarakat Perkebunan (Kimbun) - Syurya Hidayat (EKO-REGIONAL, 2007)
To achieve prosperity in regional development and revitalization society rubber plantation in Jambi Province, it needs development policy reorientation. The approach is directed by regional development by plantation society industrial program. To support the implementation program to be mutual benefit, Cooperative Commodity Development Center (CCDC) needs to establish also. It will be a forum to coordinate and communicate the regional development elements. Keywords:  revitalization, regional development, CCDC